Proportion and Determinants of Uncontrolled Hypertension among Treated Hypertensive Patients - Al-Lami, Faris (Journal of the Faculty of Medicine Baghdad, 2007)
Hypertension (HT) remains poorly controlled even in the developed countries in spite of the improvement in management. Many studies found that about 70% of people with HT remain uncontrolled. The aim of this study is to determine the proportion, and determinants of uncontrolled HT (UHT) among treated hypertensive patients. A random sample of 214 known hypertensive patients, on regular treatment for a minimum of one year was included. The mean of three blood pressure (BP) readings measured two weeks apart was considered. Controlled BP was defined as systolic BP≤140mmHg, and diastolic BP≤90 mmHg. A questionnaire was used to collect data on certain demographic variables (age, gender, marital status, educational status, crowding index), smoking habit, salt, and alcohol intake, number of used antihypertensive drugs, frequency of BP checking, co morbid illnesses, and certain anthropometric measurements. The proportion of UHT is 68%. Although the proportion of UHT was higher among older age patients, males, currently married, college graduate, those using three antihypertensive drugs, patients with no dietary salt restriction, or no co morbid illnesses, but these factors were not proved to be statistically significant. Current smoking, Body Mass Index (BMI) ≥25 Kg/m2(reflecting overweight/ Obesity), and frequency of BP checking were statistically significant predictors of UHT.